Critical Success Factors in The Infusion of Instructional Technologies for Open Learning in Development Settings: The case of the University of Botswana - Uys, Philip M. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2003)
This article seeks to identify critical success factors for the appropriate infusion of instructional technologies to advance open learning in higher education within developing settings. Describe here is a descriptive account of a two-year case study based on the author’s personal analysis of, and reflection on, factors that contributed to the infusion of instructional technologies to advance open learning at the University of Botswana. The first critical success factors identified in this article include: a clear vision, support of committed leadership, and dedicated personnel/ change agents to ensure successful project implementation. The second critical success factor identified was the need for all involved to fully appreciate and understand the systemic nature of the infusion of instructional technologies for open learning purposes, as well as garner the commitment of strategic partners working in related systems. Finally highlighted, are the requirements needed to address the complex nature of the infusion of instructional technologies into the University’s educational offerings. It is hoped that those involved in education in developing countries, and particularly those desirous of advancing open learning through the use of instructional technologies, will find this descriptive analysis useful. Indeed, those of us involved in implementing instructional technologies in developing nations are still in the initial stages of this exciting yet challenging endeavour.